Fare un passo di lato per farne due avanti - Edoardo Esposto; Giulio Moini (Quaderni di Sociologia)
The article aims to position itself within the contemporary theoretical debate on the crisis of the historical primacy of neoliberalism. Many commentators have seen in the public spending programs implemented to address the pandemic crisis a confirmation of the trend that emerged during the 2008 crisis, namely the end of the dogma of reducing public spending and forbidding any form of State intervention aimed at redistribution. These events are interpreted as the beginning of a new phase of post-neoliberalism. But is it so? Are we facing the definitive crisis and historical overcoming of neoliberalism, or are we instead facing a new variegation of it which – as has happened in other historical moments – allows this paradigm to survive and reproduce?